Analysis of Health Belief Model Factors on Parental Participation in Posyandu After Complete Basic Immunization - Agustiningrum, Rita; Rinata, Evi (Universitas Muhammadiyah Sidoarjo, 2025)
The low level of parental visits to Posyandu in Pasuruan Regency is a concern, where the coverage of complete basic immunization has only reached 53.72% in 2023. The most visits occurred in infants aged 0-6 months, but decreased significantly after that age. The Health Belief Model (HBM) was used to understand the factors that influence participation, including perceptions of vulnerability, severity, benefits, perceived barriers, cues to action, and self-efficacy. Objective: to analyze relationships implementing HBM on parental participation in Posyandu after toddlers have completed complete basic immunization. This study is an analytical study with a cross-sectional design. A sample of 61 toddlers aged 1-5 years, the sampling technique used a purposive sampling technique. Data were collected through questionnaires that had been tested for validity and reliability. Data analysis used the Spearman's rho test. The results of the analysis showed that only perceptions of benefits had a significant relationship with parental participation in Posyandu after complete basic immunization (p = 0.027; r = 0.283). Other variables such as perceived susceptibility (p = 0.198; r = 0.167), perceived severity (p = 0.849; r = -0.013), perceived barriers (p = 0.082; r = -0.243), cues to action (p = 0.062; r = 0.252), and self-efficacy (p = 0.130; r = 0.205) did not show significant relationships (p > 0.05). Perceived benefits play an important role in increasing parental participation in Posyandu after complete basic immunization. The HBM approach can strengthen these perceptions to increase visits.